Alexander Fenton - Cheape, Hugh (Proceedings of the Society of Antiquaries of Scotland, 2013)
Alexander – ‘Sandy’ – Fenton was a scholar and teacher who has had a profound influence on many areas of Scottish and European studies and museums, not least through the extensive corpus of his written and published work.